(untitled) (Research, Society and Development, 2021)
Introduction: Recent research indicates that tilapia has in its skin a non-infectious microbiota that presents good adherence to the wound bed, besides being similar to the morphological structure present in human skin. Objective: This study aims to demonstrate the efficacy of tilapia skin implantation as a possible source of biomaterial for grafting and biological dressing for the treatment of burns. Methods: The present study is a review of exploratory literature. For the searches, the following databases were used: Virtual Health Library, Scielo, Pubmed, LILACS and Medline. Papers published from 2004 to 2019 were used as eligibility criteria using the keywords "tilapia" and "burns". Articles that did not fit the objectives of this research were excluded. Results: Research has shown that the morphological profile of tilapia skin bears great resemblance to that of human skin, with collagen fibers arranged in the same consistency of the deep dermis found in human skin, soon when submitted to treatment to burned patients, the use of tilapia skin showed a recovery almost 70% better as a substitute for conventional dressing, in addition to reducing the treatment time to patients, with good results. Conclusion: Based on the research it can be concluded that tilapia skin brings a great promise of an effective and innovative product, easy to apply and high availability, with great efficacy in healing burns with decreased pain in patients.